2001
DOI: 10.1177/088307380101600302
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patients With Undetectable Anticonvulsant Blood Levels: Comparison With Compliant Patients

Abstract: Undetectable anticonvulsant blood levels indicate sustained noncompliance (several consecutive doses missed). We compared 91 consecutive outpatients with epilepsy and undetectable anticonvulsant blood levels to 100 patients seen during the same time period, verified as compliant by acceptable serum levels. We hypothesized that pay status, application for Supplemental Security Income, patient age, history of missed appointments, and functional status would differ between compliant and noncompliant patients. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…The main reasons for missing drugs were similar to what has been reported by Faris et al and Snodgrass et al respectively [16, 27]. The cost of drugs limits caregivers from purchasing them in case they are not availed at the clinic due to other priorities such as rent and food which usually override purchasing of medication thus leading to non adherence.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The main reasons for missing drugs were similar to what has been reported by Faris et al and Snodgrass et al respectively [16, 27]. The cost of drugs limits caregivers from purchasing them in case they are not availed at the clinic due to other priorities such as rent and food which usually override purchasing of medication thus leading to non adherence.…”
Section: Discussionsupporting
confidence: 74%
“…This may explain the differences in therapeutic drug levels from our study compared to other studies. [2527]. …”
Section: Discussionmentioning
confidence: 99%
“…Age, socioeconomic status, race, and family factors can also influence compliance to treatment, especially in children with asthma, epilepsy, and diabetes. [8,9] One survey among parents of children with asthma indicated that parental concerns about controller medication were associated with poor medication compliance. Parents may stop the daily inhaler for the child when their child feels better, thinking that will prevent the adverse reactions of medication.…”
Section: Reasons/barriers For Noncompliancementioning
confidence: 99%
“…This variation in the pharmacokinetics captured by TDM has been used to justify higher dosages in such patients [21, 22, 26, 27]. With respect to a noncompliant patient, this dose escalation is a potentially harmful practice as failure to verify and distinguish a noncompliant patient versus a patient with variable pharmacokinetics can lead to the overtreatment of noncompliant patients [8]. In addition to this complex scenario, it is important to realize that the variable of pharmacodynamics, or the actual patient responsiveness, is not captured by TDM and therefore provides another counter argument against its clinical usefulness [8, 28].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to a noncompliant patient, this dose escalation is a potentially harmful practice as failure to verify and distinguish a noncompliant patient versus a patient with variable pharmacokinetics can lead to the overtreatment of noncompliant patients [8]. In addition to this complex scenario, it is important to realize that the variable of pharmacodynamics, or the actual patient responsiveness, is not captured by TDM and therefore provides another counter argument against its clinical usefulness [8, 28]. In other words, some patients may remain clinically stable despite subtherapeutic serum levels of the AED simply because of variations in pharmacodynamics among patients.…”
Section: Introductionmentioning
confidence: 99%